Cd-Resistant Strains of B. cereus S5 with Endurance Capacity and Their Capacities for Cadmium Removal from Cadmium-Polluted Water. - Huiqing Wu; Qingping Wu; Guojie Wu; Qihui Gu; Linting Wei (PLoS ONE, 2016)
The goal of this study was to identify Cd-resistant bacterial strains with endurance capacity and to evaluate their ability to remove cadmium ions from cadmium-polluted water. The Bacillus cereusS5 strain identified in this study had the closest genetic relationship with B. cereus sp. Cp1 and performed well in the removal of Cd2+ions from solution. The results showed that both the live and dead biomasses of the Cd2+-tolerant B. cereus S5 strain could absorb Cd2+ ions in solution but that the live biomass of the B. cereus S5 strain outperformed the dead biomass at lower Cd2+concentrations. An analysis of the cadmium tolerance genes of B. cereus S5 identified ATPase genes that were associated with cadmium tolerance and involved in the ATP pumping mechanism. The FTIR spectra revealed the presence of amino, carboxyl and hydroxyl groups on the pristine biomass and indicated that the cadmium ion removal ability was related to the structure of the strain. The maximum absorption capacity of the B. cereus S5 strain in viable spore biomass was 70.16 mg/g (dry weight) based on a pseudo-second-order kinetic model fit to the experimental data. The Langmuir and Langmuir-Freundlich isotherm adsorption models fit the cadmium ion adsorption data well, and the kinetic curves indicated that the adsorption rate was second-order. For Cd2+ concentrations (mg/L) of 1-109 mg/L, good removal efficiency (>80%) was achieved using approximately 3.48-10.3 g/L of active spore biomass of the B. cereus S5 strain. A cadmium-tolerant bacteria-activated carbon-immobilized column could be used for a longer duration and exhibited greater treatment efficacy than the control column in the treatment of cadmium-polluted water. In addition, a toxicity assessment using mice demonstrated that the biomass of the B. cereus S5 strain and its fermentation products were non-toxic. Thus, the isolated B. cereus S5 strain can be considered an alternative biological adsorbent for use in emergency responses to severe cadmium pollution and in the routine treatment of trace cadmium pollution.